Hydroxyapatite-alginate Based Matrices for Drug Delivery - Nayak, Amit K.; Hasnain, Md. S.; Nanda, Sitansu S.; Yi, Dong K. (Current Pharmaceutical Design, 2019)
Background: Hydroxyapatite (HAp) is a biocompatible bioceramic compound by nature and widely utilized in a broad range of biomedical applications, especially in drug delivery, tissue engineering, orthopedics, dentistry, etc. To intensify its usage, HAp is being reinforced with different biopolymer(s). In these bioceramicbiopolymeric systems, HAp crystallites have been well inviolate with the alginate molecules. The objective of this review article is to present a comprehensive discussion of different recently researched drug-releasing potential by HAp-alginate based matrices. Methods: During past few years, HAp particles (both synthesized and naturally derived) have been reinforced within different alginate-based systems to load a variety of drug candidates. Most of the reported drug-releasing HAp-alginate based matrices were prepared by the methodology of ionic-gelation of sodium alginate followed by air-drying/spray drying process. Results: HAp-alginate systems have already been proved as useful for loading a variety of drugs and also resulting sustained drug delivery with minimizing the drawbacks of pure alginate matrices (such as burst drug-releasing and low mechanical property in the alkaline pH). Conclusion: HAp-alginate composites loaded with different kinds of drugs have already been reported to exhibit sustained releasing of loaded drugs over a longer period.
Keywords: alginate based matrices